PARADIGMA PANCASILA SEBAGAI UPAYA PENGUATAN SIKAP TOLERANSI ANTAR SUKU DI KABUPATEN OKU TIMUR (STUDI KASUS MAHASISWA UNIVERSITAS NURUL HUDA) - Anisa Ulkhusnah; Muhammad Nanang Rifa'i; Zulaikah Zulaikah (Prodi PPKn Universitas Slamet Riyadi, 2026)
This study was carried out to explore the application of Pancasila as a paradigm for strengthen tolerance among ethnic groups of students at Nurul Huda University Sukaraja. The method used is a qualitative methode with a descriptive approace through interviews and case study with some of student of Nurul Huda University who come from different ethnicities. The results of this study indicate the high attitude of tolerance among students at Nurul Huda University which is based on a sense of compatriots' fate so that the longer the relationship, the higher the sense of tolerance and solidarity that is created. This study prove the application of Pancasila as a paradigm in the attitude of tolerance carried out in the campus environment in terms of accepting opinions between students, not offending, having an attitude of helping each other, high sense of solidarity, respecting each other despite being of different ethnicity, and acting wisely in making decisions.